2010
DOI: 10.1002/anie.201002082
|View full text |Cite
|
Sign up to set email alerts
|

Isophthalic Acid: A Basis for Highly Ordered Monolayers

Abstract: Standing on their own two feet: Underpotential deposition of Cu on Au(111) yields a surface onto which 1,3‐benzenedicarboxylic acid (IPA) and 1,3,5‐benzenetricarboxylic acid (TMA) adsorb in a bipodal configuration. Both molecules form highly crystalline isostructural monolayers, thus demonstrating the potential of the IPA moiety as tecton for self‐assembled monolayers. A thin film of a Cu–TMA coordination polymer was grown on a patterned TMA monolayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(67 citation statements)
references
References 37 publications
(54 reference statements)
7
59
0
1
Order By: Relevance
“…It is noted that in the case of BPTCA the intensity ratio of the carboxylate oxygen and the C-OH/C=O signals is significantly smaller compared to the analogue TMA 41 because of the stronger attenuation of the carboxylate signal from the buried SAM-substrate interface by the additional benzene ring. In summary, the XPS data corroborate the analogy between TMA [41][42] and BPTCA with respect to the substrate dependent bonding configuration.…”
Section: Xpssupporting
confidence: 74%
See 2 more Smart Citations
“…It is noted that in the case of BPTCA the intensity ratio of the carboxylate oxygen and the C-OH/C=O signals is significantly smaller compared to the analogue TMA 41 because of the stronger attenuation of the carboxylate signal from the buried SAM-substrate interface by the additional benzene ring. In summary, the XPS data corroborate the analogy between TMA [41][42] and BPTCA with respect to the substrate dependent bonding configuration.…”
Section: Xpssupporting
confidence: 74%
“…Since for TMA such a flat lying structure has not been observed [41][42][43] we suspected that the additional benzene ring of BPTCA might shift the equilibrium from the tilted geometry observed for TMA towards the flat lying phase due to the additional interaction of the second aromatic ring with the substrate. Indeed, upon a further significant increase in the preparation temperature, islands exhibiting the row structure familiar from TMA started to form and, within a rather narrow temperature range of about 10°C, a pronounced improvement in the film structure was observed, as evident from the comparison of Figures 4c and 4d.…”
Section: Stmmentioning
confidence: 98%
See 1 more Smart Citation
“…The C 1s spectra have been decomposed into components characteristic of emissions from COOH (~288.5 eV), COO -(~287 eV) and the aromatic ring carbons (284-284.5 eV). 24,[35][36][37][65][66] Following previous work on SAMs of molecules featuring an isophthalic acid moiety, all spectra were fitted with one component for each signal with the exception of the main emission, which has an additional small component located at2 85.2 eV with an area of 2-6 % of the main peak. [35][36][37][38] The origin of this small feature is not fully clear.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] To this small set of spectroscopic studies, benzene-1,3-dicarboxylic acid (isophthalic acid, IPA), benzene-1,3,5-tricarboxylic acid (trimesic acid, TMA) and biphenyl-3,4′,5-tricarboxylic acid (BPTCA) have recently been added. [35][36][37][38] Employing a combination of X-ray spectroscopies and scanning tunneling microscopy at molecular resolution, these studies revealed that ordered layers are formed on Cu and Ag prepared as underpotential deposited layers on Au. Apart from providing insights into the very initial stages of thin film * There are varying interpretations of the term self-assembled monolayer.…”
Section: Introductionmentioning
confidence: 99%